Calcination-Dependent Morphology Transformation of Sol-Gel- Synthesized MgO Nanoparticles - Jeevanandam, J.; Chan, Stephanie; Danquah, M. (Wiley - V C H Verlag GmbH & Co. KGaA, 2017)
© 2017 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim Sol-gel synthesis is a widely accepted method of producing nanoparticles with high surface area-to-volume ratio and purity at relatively low temperatures. For metal oxide nanoparticle synthesis, sol-gel maintains a good metal oxide composition with controlled chemical structure and the ability to fine-tune morphology and size. Magnesium oxide (MgO) nanoparticles possess unique physicochemical characteristics that have enabled a wide range of applications from catalysis to disease treatment. The potential features of MgO nanoparticles are significantly affected by their shape and size. However, research investigating the thermo-molecular mechanisms governing the size and shape formation of MgO nanoparticles during sol-gel synthesis is limited. This study investigates the effect of sol-gel synthesis conditions on the shape and size as well as other functional features of MgO nanoparticles. The results demonstrated that the size and shape alterations of MgO nanoparticles were dependent on changes in calcination temperature and also the presence of periclase phase along with their crystallinity and functional groups. TEM analysis showed the morphological evolution during the synthesis process from spherical to hexagonal and from hexagonal to rod shape. By varying the calcination temperature and gelling agent composition in sol-gel synthesis, MgO nanoparticles with different size distributions and morphologies can be generated for various applications. The current study reveals that the gelling agent is responsible for sol-gel phase formation which eventually affects the calcination temperature for the formation of morphologically different MgO nanoparticles.